2020
DOI: 10.1111/jcmm.15667
|View full text |Cite
|
Sign up to set email alerts
|

LINC00941 promotes oral squamous cell carcinoma progression via activating CAPRIN2 and canonical WNT/β‐catenin signaling pathway

Abstract: Dysregulation of long non‐coding RNAs (lncRNAs) has been implicated in many cancer developments. Previous studies showed that lncRNA LINC00941 was aberrantly expressed in oral squamous cell carcinoma (OSCC). However, its role in OSCC development remains elusive. In this study, we demonstrated that in OSCC cells, EP300 activates LINC00941 transcription through up‐regulating its promoter H3K27ac modification. Up‐regulated LINC00941 in turn activates CAPRIN2 expression by looping to CAPRIN2 promoter. Functional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 45 publications
4
26
0
Order By: Relevance
“…Some studies have shown that it can promote the growth and metastasis of many tumors. In oral squamous cell carcinoma, the Wnt/β-catenin signal transduction pathway was activated by highly expressed LINC00941; 22 the up-regulation of LINC00941 can accelerate the development of hepatocellular carcinoma by promoting epithelial-mesenchymal transition (EMT) and malignancy. 23 LINC00941 was highly expressed in gastric cancer, which was related to its biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that it can promote the growth and metastasis of many tumors. In oral squamous cell carcinoma, the Wnt/β-catenin signal transduction pathway was activated by highly expressed LINC00941; 22 the up-regulation of LINC00941 can accelerate the development of hepatocellular carcinoma by promoting epithelial-mesenchymal transition (EMT) and malignancy. 23 LINC00941 was highly expressed in gastric cancer, which was related to its biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that CAPRIN2 has roles in the inhibition of cell growth, differentiation, the enhancement of classical WNT signaling and the maintenance of dendritic structure [ 36 ]. CAPRIN2 is considered to be an oncoprotein in hepatoblastoma [ 37 ] and can induce the development of oral squamous cell carcinoma via activating the WNT/β-catenin signaling pathway [ 38 ]. In the present research, we displayed for the first time that CAPRIN2 was significantly upregulated in CRC cells, which was consistent with the results of the tissue level on the online dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, upregulated LINC00941 could in turn activate the expression of its nearby gene CAPRIN2 , whereas chromatin organizer CTCF was required for this LINC00941 -induced CAPRIN2 overexpression. As CTCF has been shown to mediate the looping of the chromatin fragment between LINC00941 and CAPRIN2 genes through its binding sites being enriched within this region, these results suggested that LINC00941 might induce CAPRIN2 expression through CTCF-mediated DNA looping [ 39 ] ( Figure 1 b).…”
Section: Mechanism Of Oral Cancer-associated Lncrnas In Tumorigenesismentioning
confidence: 99%
“…This study not only supports the involvement of lncRNAs in Wnt signaling regulation, but also reveals the potential therapeutic value of CAFs. Meanwhile, the aforementioned lncRNA LINC00941 could provoke canonical Wnt signaling via upregulating the expression of Caprin-2 [ 39 ], a positive regulator of Wnt signaling, by promoting GSK3-depedent LRP5/6 phosphorylation ( Figure 2 a), and thereby promoting OSCC progression [ 141 ].…”
Section: Lncrnas Involved In Crucial Signaling Pathwaysmentioning
confidence: 99%